Domestication of Rasbora argyrotaenia from the Musi river waters. (November 2019) - Mutiara, D; Harris, H; Arsyad, N
Abstract: The domestication of Seluang fish (Rasbora argyrotaenia) has been carried out from the waters of the Musi river in the province of South Sumatra. The aim of determining the original domestication technique as a basic for further research on reproduction or spawning of Seluang fish in bulk and planned and restocking in public waters as an effort to preserve Seluang fish resources. The sampling location was used the Purposive Random Sampling method in 3 locations where there are usually many Seluang fish. Whereas the domestication method used the Experimental method with environmental manipulation treatment in cement tubs measuring 3 × 4 m deep 0.75 m. Fish are given natural and artificial feed for approximately 1 month (week 0 to week 4). The results showed that the domestication process of Seluang Fish ( Rasbora argyrotaenia ) can be done by maintenance in ponds that have been manipulated to resemble their natural habitat with artificial feed. The results showed an increase in weight of 0.0114 grams / day, an increase in length of 0.036 cm / day and survival of 79.01%.